Extending the performance of net shape molded fiber reinforced polymer composite valves for use in internal combustion engines - Buckley, Richard Theodore, author; Stanglmaier, Rudolf, advisor; Radford, Donald, advisor (Colorado State University. Libraries, 2007)
Fiber Reinforced Composite (FRC) materials offer the possibility of reduced mass and increased structural performance over conventional metals. When used in reciprocating components of internal combustion engines, this may enable increased power and mechanical efficiency. Previously published work on FRC engine valves has both shown structural and thermal limitations.

A net-shape resin transfer molded intake valve has been developed, using a single-piece carbon fiber preform and the high temperature polymer PETI-RFI. Structural design issues have been overcome. Performance has been validated through static testing and dynamic testing. Testing culminated with an intake valve operating for four hundred continuous minutes in an engine without failure.

High engine load conditions resulted in thermal failure of FRC valves. Extensive thermal modeling was conducted to simulate the effect of fiber orientation and coating combinations on transient thermal performance of FRCs. One dimensional modeling has predicted FRC valve surface temperatures to be 120°C higher than that of a steel valve. Simply re-orienting conductive fiber along the heat path may reduce the temperature rise to below that of steel.

Two dimensional transient FRC and coatings thermal analysis has resulted in a novel method of evaluating thermal performance. Using the unitless ratio of thermal resistance at the coating surface and at the interface boundary, designed Bb, an accurate prediction of the interface temperature can be obtained. From this, relative temperature gradients in both the coating and core materials can also be estimated. Analysis shows that the values of Bb1, interface temperature is lower, a large temperature gradient exists in the coating, and the core material is more thermally isolated. Testing of coupon samples in the cylinder head of a running engine has verified the trends shown. Using this methodology a fiber and coating structure is proposed that reduces FRC core temperature by 80%. It has been shown through analysis and experimentation that careful selection of fiber orientation and coating materials can enable a polymer matrix composite material to withstand the structural and thermal environment of an IC engine combustion chamber.
Keywords: composite valves; fiber-reinforced polymers; heat transfer; internal combustion engines; shape molded fiber; automotive materials; mechanical engineering; automotive engineering